Multiphoton microscopy assessment of the structure and variability changes of dermal connective tissue in vulvar lichen sclerosus: A pilot study. Issue 9 (8th July 2022) - Potapov, Arseniy L.; Sirotkina, Marina A.; Matveev, Lev A.; Dudenkova, Varvara V.; Elagin, Vadim V.; Kuznetsov, Sergey S.; Karabut, Maria M.; Komarova, Anastasia D.; Vagapova, Nailya N.; Safonov, Ivan K.; Kuznetsova, Irina A.; Radenska‐Lopovok, Stefka G.; et al.
Abstract: In this article, we offer a novel classification of progressive changes in the connective tissue of dermis in vulvar lichen sclerosus (VLS) relying on quantitative assessment of the second harmonic generation (SHG) signal received from formalin fixed and deparaffinized tissue sections. We formulate criteria for distinguishing four degrees of VLS development: Initial‐Mild‐Moderate‐Severe. Five quantitative characteristics (length and thickness type I Collagen fibers, Mean SHG signal intensity, Skewness and Coherence SHG signal) are used to describe the sequential degradation of connective tissue (changes in the structure, orientation, shape and density of collagen fibers) up to the formation of specific homogeneous masses. Each of the degrees has a characteristic set of quantitatively expressed features. We focus on the identification and description of early, initial changes of the dermis as the least specific. The results obtained by us and the proposed classification of the degrees of the disease can be used to objectify the dynamics of tissue changes during treatment. Abstract : In this article, we offer a novel classification of sequential degradation of dermal connective tissue in vulvar lichen sclerosus relying on a quantitative assessment of the second harmonic generation from a high‐resolution method of multiphoton microscopy. Emphasis was placed on the identification and description of early, initial changes in the dermis as the least specific and more successful for therapy.